2020
DOI: 10.1186/s12931-020-01597-5
|View full text |Cite
|
Sign up to set email alerts
|

High expression level of serpin peptidase inhibitor clade E member 2 is associated with poor prognosis in lung adenocarcinoma

Abstract: Background Recent studies have revealed that serpin peptidase inhibitor clade E member 2 (SERPINE2) is associated with tumorigenesis. However, SERPINE2 expression and its role in lung adenocarcinomas are still unknown. Methods The expression levels of SERPINE2 in 74 consecutively resected lung adenocarcinomas were analyzed by using immunostaining. Inhibition of SERPINE2 expression by small interfering RNA (siRNA) was detected by quantitative PCR. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Numerous studies have reported SERPINE2 overexpression in various cancers, which has been associated with the degree of cancer malignancy [8,[14][15][16][17][18][19][20][21][22][24][25][26]. Utilizing the TCGA database, this study detected higher SERPINE2 mRNA expression in UBUC, which has been associated with poor survival.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Numerous studies have reported SERPINE2 overexpression in various cancers, which has been associated with the degree of cancer malignancy [8,[14][15][16][17][18][19][20][21][22][24][25][26]. Utilizing the TCGA database, this study detected higher SERPINE2 mRNA expression in UBUC, which has been associated with poor survival.…”
Section: Discussionmentioning
confidence: 73%
“…As a serine protease inhibitor, SERPINE2 has been known for its anti-serine protease activity against thrombin, urokinase, plasminogen, and other serine proteinases [11][12][13]. Tumor cells have also been found to secrete SERPINE2, with studies showing that abnormal expression of SERPINE2 contributes to tumorigenesis and tumor invasion in various cancers, including breast cancer, pancreatic cancer, colorectal cancer, gastric cancer, testicular cancer, skin melanoma, osteosarcoma, thyroid cancer, oral squamous cell carcinoma, endometrial cancer, esophageal squamous cell carcinoma, lung adenocarcinoma, and hepatocellular cell carcinoma [8,[14][15][16][17][18][19][20][21][22][23][24][25][26]. A recent study on UBUC demonstrated that SERPINE2 might play important roles in activating and recruiting immune cells, which can significantly impact tumor behavior regulation and treatment response [27].…”
Section: Introductionmentioning
confidence: 99%
“…The mouse model of breast tumor heterogeneity demonstrated that SERPINE2 provokes tumor cells to form vascular networks that mimic blood vessels to facilitate tumor cells penetration and metastasis, indicating that SERPINE2 is a dominant driver of metastatic progression [ 30 ]. Simultaneously, high SERPINE2 expression was an independent poor prognostic factor in oral squamous cell carcinoma (OSCC), lung adenocarcinoma, urothelial carcinoma and endometrial cancer [ 31 , 32 , 33 , 34 ], and SERPINE2 was identified as a promising therapeutic target in melanoma metastasis and in the radio-resistance of lung cancer. SERPINE2 promotes radio resistance by mediating the interaction of MRE11 with ATM to induce ATM phosphorylation in homologous recombination (HR)-mediated double strand break (DSB) repair [ 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serine protease inhibitors (SERPINS) are a superfamily of homologous proteins that have important roles in inflammation, immune-system function, apoptosis regulation [ 5 , 6 ], and metastasis of cancer cells [ 7 ]. Human SERPINS are divided into nine groups (A–I) called “clades” according to their sequence similarity.…”
Section: Introductionmentioning
confidence: 99%